2018
DOI: 10.1007/s10649-017-9797-9
|View full text |Cite
|
Sign up to set email alerts
|

Meanings given to algebraic symbolism in problem-posing

Abstract: Some errors in the learning of algebra suggest students have difficulties giving meaning to algebraic symbolism. In this paper, we use problem posing in order to analyze the students' capacity to assign meaning to algebraic symbolism and the difficulties that students encounter in this process depending on the characteristics of the algebraic statements given. We designed a written questionnaire composed of eight closed algebraic statements expressed symbolically, which was administered to 55 students who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…These steps included (1) borrowing from the tens column, (2) subtracting 4 from the ones column, (3) borrowing from the hundreds column, (4) taking away 6 from the tens column, and (5) taking away 1 from the hundreds column. The focus on procedural knowledge in mathematics classes has been criticized as one reason for students' difficulty in understanding the meaning of equations or adopting efficient problemsolving strategies for new or complex problems (Cañadas, Molina, & del Río, 2018;Jacobs et al, 2007;Peled & Segalis, 2005). Similarly, in science classrooms, researchers have found that students tend to rely on algorithms without conceptual understanding of the science in solving problems and teachers tend to focus instruction on using mathematical procedures to do calculation (Bain, Rodriguez, & Towns, 2019b;Bing & Redish, 2007;Hansson et al, 2015;Hu & Rebello, 2013;Kuo et al, 2013;Lehavi et al, 2017;Redish, 2017;Redish & Gupta, 2010;Redish & Kuo, 2015;Schuchardt, 2016;Schuchardt & Schunn, 2016;Tuminaro & Redish, 2007;Wink & Ryan, 2019).…”
Section: Math-procedures Sensemakingmentioning
confidence: 99%
See 3 more Smart Citations
“…These steps included (1) borrowing from the tens column, (2) subtracting 4 from the ones column, (3) borrowing from the hundreds column, (4) taking away 6 from the tens column, and (5) taking away 1 from the hundreds column. The focus on procedural knowledge in mathematics classes has been criticized as one reason for students' difficulty in understanding the meaning of equations or adopting efficient problemsolving strategies for new or complex problems (Cañadas, Molina, & del Río, 2018;Jacobs et al, 2007;Peled & Segalis, 2005). Similarly, in science classrooms, researchers have found that students tend to rely on algorithms without conceptual understanding of the science in solving problems and teachers tend to focus instruction on using mathematical procedures to do calculation (Bain, Rodriguez, & Towns, 2019b;Bing & Redish, 2007;Hansson et al, 2015;Hu & Rebello, 2013;Kuo et al, 2013;Lehavi et al, 2017;Redish, 2017;Redish & Gupta, 2010;Redish & Kuo, 2015;Schuchardt, 2016;Schuchardt & Schunn, 2016;Tuminaro & Redish, 2007;Wink & Ryan, 2019).…”
Section: Math-procedures Sensemakingmentioning
confidence: 99%
“…In the Math-Structure sensemaking category, the focus is on understanding the arrangement of variables (symbols) and operations of the mathematical equations (Bain, Rodriguez, & Towns, 2019a, 2019bBecker & Towns, 2012;Bing & Redish, 2007;Brahmia et al, 2016;Cañadas et al, 2018;Hestenes, 2010;J. Hiebert & Lefevre, 1986;Hu & Rebello, 2013;Izsák, 2004;Jacobs et al, 2007;Karam, 2014;Karam & Krey, 2015;Kirshner, 1989;Kuo et al, 2013;Moss & Case, 1999;Pospiech, 2019;Redish, 2017;Redish & Kuo, 2015;Rodriguez et al, 2019;Rodriguez et al, 2018;Schuchardt & Schunn, 2016;Sherin, 2001).…”
Section: Math-structure Sensemakingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although such conditions can spawn a diversity of topics, a specific mathematical theme can similarly be employed. For instance, Canadas et al (2018) present situations using algebraic statements to extend mathematical thinking as opposed to performing meaningless operations on equations. Table 1 displays posed problems from the previous research.…”
Section: Introductionmentioning
confidence: 99%